The impact of miR-9 in osteosarcoma: A study based on meta-analysis, TCGA data, and bioinformatics analysis. Issue 35 (28th August 2020) - Wu, Fengfeng; Jiang, Xuesheng; Wang, Qun; Lu, Qian; He, Fengxiang; Li, Jianyou; Li, Xiongfeng; Jin, Mingchao; Xu, Juntao
Abstract : Abstract: The function of miR-9 in osteosarcoma is not well-investigated and controversial. Therefore, we conducted meta-analysis to explore the role of miR-9 in osteosarcoma, and collected relevant TCGA data to further testify the result. In addition, bioinformatics analysis was conducted to investigate the mechanism and related pathways of miR-9-3p in osteosarcoma. Literature search was operated on databases up to February 19, 2020, including PubMed, Web of Science, Science Direct, Cochrane Central Register of Controlled Trials, and Wiley Online Library, China National Knowledge Infrastructure, China Biology Medicine disc, Chongqing VIP, and Wan Fang Data. The relation of miR-9 expression with survival outcome was estimated by hazard ratio (HRs) and 95% CIs. Meta-analysis was conducted on the Stata 12.0 (Stata Corporation, TX). To further assess the function of miR-9 in osteosarcoma, relevant data from the TCGA database was collected. Three databases, miRDB, miRPathDB 2.0, and Targetscan 7.2, were used for prediction of target genes. Genes present in these 3 databases were considered as predicted target genes of miR-9-3p. Venny 2.1 were used for intersection analysis. Subsequently, GO, KEGG, and PPI network analysis were conducted based on the overlapping target genes of miR-9-3p to explore the possible molecular mechanism in osteosarcoma. Meta-analysis shown that overexpression of miR-9 was associated with worse overall survival (OS) (HR = 4.180, 95% CI: 2.880–6.066, P  < .001, I 2  = 23.5%). Based on TCGA data, osteosarcoma patients with overexpression of miR-9-3p (HR = 1.603, 95% CI: 1.028–2.499, P  = .037) and miR-9-5p (HR = 1.698, 95% CI: 1.133–2.545, P  = .01) also suffered poor OS. In bioinformatics analysis, 2 significant and important pathways were enriched: Wnt signaling pathway from gene ontology analysis (gene ontology:0016055, P -adjust = .008); hippo signaling pathway from Kyoto Encyclopedia of Genes and Genomes analysis ( P -adjust = .007). Moreover, network analysis relevant protein-protein interaction was visualized, revealing 117 nodes and 161 edges. High miR-9 expression was associated with poor prognosis. Based on bioinformatics analysis, this study enhanced the understanding of the mechanism and related pathways of miR-9 in osteosarcoma. Abstract : Supplemental Digital Content is available in the text